3D Nanostructuring of Phase-Change Materials Using Focused Ion Beam toward Versatile Optoelectronics Applications - Yimam, Daniel T (Advanced materials (Deerfield Beach, Fla.), 2024)
© 2024 The Authors. Advanced Materials published by Wiley‐VCH GmbH.